The Rorschach Psychodiagnostic in single-parent families - Frisancho Vera, Dora (1999)
It is analyzed the personality of the children that belong to families with only one parent. Making use of the Rorschach Psychodiagnostic -Exner 1978 version-, are compared the variables of the test in two groups of children, one of complete families and other of only one parent. The differences calculated with statistic meaning propose a Rorschach frame in pre-morbid conditions that it can derive from the breeding within incomplete families and that would undermine in incipient manner the psychic stability. This result shares with other authors the probable presence of a depressive inner component.